Reformasi Hukum Keluarga di Era Disrupsi: Menyikapi Perkembangan Digital Dalam Isu Pernikahan dan Perceraian - Novri Hanafiah; Surya Sukti; Mustar (Jurnal Riset Multidisiplin Edukasi, 2025)
The advancement of digital technology has significantly transformed the dynamics of family law, particularly in the contexts of marriage and divorce. Interactions that once required physical presence have increasingly shifted to digital spaces through matchmaking applications, social media, and other online communication platforms. This phenomenon poses new challenges for family law, which traditionally relies on physical evidence and conventional norms, especially regarding the recognition of digital evidence and the legality of online marriages. This study employs a normative-empirical approach using literature review, legal regulation analysis, and case studies to explore how family law can adapt to digital developments. It reveals that ontological, epistemological, and axiological challenges must be addressed through legal reforms that consider digital access equity, data privacy protection, and the validity of digital evidence. Family law reform must not only align legal procedures with technological progress but also uphold moral values and justice within the family institution. The study recommends updating regulations to accommodate digital transformation while preserving the foundational principles of family law.